소송문서의 전자적 유통을 위한 XMP 기반 전자문서 구조 설계 - 박민수(Min-Soo Park); 송충근(Choong-Geun Song); 이남용(Nam-Young Lee); 김종배(Jong-Bae Kim) (디지털콘텐츠학회논문지, 2011)
각종 업무처리시스템이 웹기반으로 구현되는 것이 보편화됨에 따라 전자소송분야에서도 이에 대한 적용이 활발하다. 소송기록을 중심으로 하는 전자소송에서는 웹상에서 전자문서를 안전하게 유통․활용하기 위해서 기록으로서의 원본성, 사건으로서의 특수성 및 위변조 방지 등의 보안성을 고려하여 전자문서 구조가 설계되어야 한다. 본 논문은 소송기록으로 적합한 전자문서 포맷과 특수한 사건정보를 관리하기 위한 XMP 및 전자문서 유통을 위한 보안요소의 연구를 통하여 헌법재판분야의 전자소송 구현시 적합한 전자문서 구조를 설계하고, 적용된 결과를 분석하였다. 본 연구는 웹상에서 전자문서 교환을 통해서 업무처리를 구현하고자 하는 경우에 유용한 참고 자료가 될 것이다. It has become commonplace to use web-based business process systems in a variety of fields, and electronic litigation is not an exception. In electronic procedures where court records are at the core of the system, the electronic document architecture should be designed in a way that electronic documents are safely circulated and utilized on the web with a consideration of the authentication of records, particularity of cases and document security such as prevention of forgery or falsification. Based on a study of electronic formats suitable for court records, the Extensible Markup Language (XMP) for management of special case information and security requirements for circulation of electronic documents, this paper suggests an adequate architecture for electronic documents designed for electronic litigation involving constitutional matters and looks into cases where such architectures are applied. The studies in this paper will serve as a useful reference for those planning to realize web-based business process that enables exchanges of electronic documents. KCI Citation Count: 0